2012
DOI: 10.3382/ps.2012-02437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feed-borne Fusarium mycotoxins with or without yeast cell wall adsorbent on organ weight, serum biochemistry, and immunological parameters of broiler chickens

Abstract: The objectives of the present study were to investigate the toxicity of feed-borne Fusarium mycotoxins on organ weight, serum biochemistry, and immunological parameters of broiler chickens and to evaluate the efficacy of yeast cell wall adsorbent in preventing mycotoxin-induced adverse effects. In total, 300 one-day-old vaccinated (Marek's disease and infectious bronchitis) Arbor Acres broiler chickens (mixed sex) were randomly divided into 3 treatments (5 repetitions per treatment) and fed basal diet and natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 36 publications
2
26
0
5
Order By: Relevance
“…Moreover, in this study, RH had no effect on the relative weight of the spleen; 85% RH decreased the relative weights of the thymus and BF in the third week of exposure. Previous reports also had inconsistent results about the effect of stress on the thymus, spleen, and BF (Quinteiro-Filho et al, 2010Li et al, 2012). Quinteiro-Filho et al (2010) showed that long-term (7 days) heat stress decreased the relative weights of the thymus, spleen, and BF, and Quinteiro-Filho et al (2012) also found that acute (10 h) heat stress had no effect on the relative weights of the same lymphoid organs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in this study, RH had no effect on the relative weight of the spleen; 85% RH decreased the relative weights of the thymus and BF in the third week of exposure. Previous reports also had inconsistent results about the effect of stress on the thymus, spleen, and BF (Quinteiro-Filho et al, 2010Li et al, 2012). Quinteiro-Filho et al (2010) showed that long-term (7 days) heat stress decreased the relative weights of the thymus, spleen, and BF, and Quinteiro-Filho et al (2012) also found that acute (10 h) heat stress had no effect on the relative weights of the same lymphoid organs.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced relative weight of lymphoid organs may be related to the necrosis and cellular depletion created by mycotoxins (Hoerr et al 1981). Moreover, effects of fusarium-born mycotoxins like DON on liver and bursa of Fabrisius have been previously studied in broilers (Swamy et al 2004;Li et al 2012) and turkeys (Girish et al 2008). In these studies as data showed contradictory results, authors concluded that organ weights might not be a proper indicator of fusarium mycotoxins toxicity and also effect of these toxins on organ weights is species, toxin and dosage dependent (Swamy et al 2004;Li et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, effects of fusarium-born mycotoxins like DON on liver and bursa of Fabrisius have been previously studied in broilers (Swamy et al 2004;Li et al 2012) and turkeys (Girish et al 2008). In these studies as data showed contradictory results, authors concluded that organ weights might not be a proper indicator of fusarium mycotoxins toxicity and also effect of these toxins on organ weights is species, toxin and dosage dependent (Swamy et al 2004;Li et al 2012). The presented background indicates that the main reason for organ weight variations in this trial might be attributed to aspergillus-born mycotoxins especially aflatoxin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the acute mode of action of YCW is not clear, Raju and Devegowda (2000) hypothesized that mycotoxin molecule might be attached to glucomannan matrix from YCW which prevents toxin absorption from intestinal tract and the subsequent toxin-induced tissue damages. Previous studies in our laboratory indicated that dietary addition of YCW at the level of 0.20% to naturally contaminated diets caused a protective effect on liver and spleen at 21 day of age, relative weight of bursa of fabricius and thymus at 42 day of age, antibody titers of Newcastle disease at both 28 and 42 day of age of broilers (Li et al, 2012;Jiang et al, 2014).…”
Section: Discussionmentioning
confidence: 75%